Fundamental Of Enterpreneurship (ENT 300) : The Workout Garage Sdn Bhd / Liyana Batrisyia Binti Nazarudin … [et al.] - Nazarudin, Liyana Batrisyia; Mohamad Iskander, Nurul Harisha; Damian, Vanaessa Evangelista; Tennent, Connielia; Syied Malek Faisal, Syied Hamiduddin Husaini; Mahdi @ Salleh, Sarmiza (2019)
The Workout Garage was founded in 2019 by a group of six friends namely Liyana Batrisyia, Vanaessa Evangelista, Sarmiza, Nurul Harisha, Connielia and Syied Hamiduddin. The reason why they came up with this business is because they see the needs and trends among the students of Universiti Teknologi Mara Kampus Samarahan 2. Most of the students like to go to the gym during their leisure time but however most of the gyms are located at Desa Ilmu and unlike Universiti Teknologi Mara Kampus Samarahan, Universiti Teknologi Mara Kampus Samarahan 2 does not have a personalized gym for the students and staffs.